Neutrosophic statistical analysis of cardiovascular disease prevention from a physical culture in urban communities - Dennys Raúl Dupotey Hernández; Darvin Manuel Ramíerez Guerra (Neutrosophic Sets and Systems)
The research presented here considers the educational potential of physical activities for dis ease prevention. Its objective is to elaborate a physical-educational intervention strategy for the preven tion of cardiovascular diseases in urban communities in the department of Cundinamarca, Colombia. The research was carried out in the municipalities of Funza, Fusagasugá Albán, and Supatá in the de partment of Cundinamarca in Colombia, based on the theoretical foundations of prophylactic and ther apeutic physical culture and related sciences for disease prevention. Theoretical, empirical, and mathe matical-statistical scientific methods were applied. In addition, neutrosophic techniques were used to validate the study. The results indicate an adequate level of statistical significance. Future work should focus on expanding the use of neutrosophic methods to enhance cardiovascular disease prevention ef forts across diverse and vulnerable populations, improving decision-making and adaptability in com munity health programs.